Rejuvenation technology in litchi is economical too - Kumar, Rajesh (Indian Horticulture, 2015)
At the initial level of adoption, the invasive rejuvenation technology for old senile fruit trees, particularly in litchi presents many (a variety) crosscutting issues on the theme of restoration of youthful vigour, enhancement of quantum of quality fruit production, period of sustainability and above all the economic feasibility. It encompasses aspects of scientific, suitability, productivity, sustainability and economic feasibility. All these require proper implementation leading to success stories. Apart from the awareness to growers and enough knowledge base through training, understanding/analysis the economic feasibility is very vital toincrease the level of adoption of this technology for profitability andprosperity.